PRÁCTICAS MATERNALES EN LA DOCENCIA DE LA ENSEÑANZA BÁSICA: ESTUDIO DE CASO - Leiva Díaz, Viriam (2005)
This is a qualitative study.  The primary objective was to analyze the mother-like teaching roll in the classroom.  The data was collected and analyzed using hermeneutic phenomenology and gender perspective methods. It was evident that in their work, teachers adopt a prolongation of the maternal attitude.  The children’s perception is similar, since they receive a teachers’ image that resembles their own mothers.  According to the teachers, their professional and maternal strengths are both socially assigned.   Thus, the school is a cultural environment that defines and reinforces people’s characteristics according to their gender.  Those conditions transfer and promote gender inequalities.